Methodological approach to estimation of the structure of load bearing insulation materials of buildings and constructions of railway transport - A. I. Adilkhodzhaev; S. S. Shaumarov; E. V. Shchipacheva; N. I. Begmatov (Вестник Научно-исследовательского института железнодорожного транспорта, 2019)
The article considers the question of the development of a new methodological approach to the creation of a heat-insulating constructional building material for external enclosing structures of buildings and constructions of railway transport. As the strength of cellular concrete is directly proportional to the average density, and the thermal properties are inversely proportional, solution to the problem of optimizing macrostructure of material in order to simultaneously improve its strength and thermal properties is much more complicated. In addition, when optimizing the properties of cellular concrete, it is necessary to vary the components that form it. Thus, optimization, ultimately, is reduced to solving a multifunctional problem with variable multicomponent parameters. Solving the problem of optimizing macrostructure of cellular concrete on the basis of an experiment using the “trial and error” method is very expensive. Moreover, even an experiment based on some technological approach does not guarantee a positive result for the values of average density taken in a reasonably wide range. Given that the thermal properties of cellular concrete are closely related not only to its average density and, consequently, to average porosity, but also to the pore size distribution and structure features in general, the method of estimating pore structure of the material in a simple and accessible way is of particular interest. A numerical experiment was performed in which the structure of cellular concrete was modeled to conditions close to real samples. To do this, using a random number generator for a given range of sizes of spherical pores and a given percentage of porosity, the structure of cellular concrete was modeled. The modeling results were analyzed on the basis of the constructed histograms for a given percentage of pores in the entire considered range (from 10 to 90 %). Results of model calculations were approximated by Gauss curves (normal law of probability distribution) and Cauchy – Lorentz curves. Thus, the new methodological approach to estimating structure of cellular concrete, based on the use of the modern approach from the standpoint of information technology, is quite accurate in defining and in its practical implementation much simpler than classical research methods.